The Influence of Visual, Auditory, and Kinesthetic Learning Styles on Students’ Learning Outcomes in Islamic Education-Based Madrasah Ibtidaiyah - Siti Mafridatul Mahbubah; Didit Darmawan (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This research is motivated by the importance of understanding the learning styles or learning modalities possessed by each student in the learning process. Each student has a different learning style, such as visual, auditory, and kinesthetic, so teachers and parents need to understand these characteristics so that the process of delivering and receiving learning materials can take place effectively. Understanding students' learning styles can also help teachers in determining learning methods, strategies, and media that are appropriate to students' needs so that students can more easily understand the subject matter, be more active in learning activities, and be able to increase motivation and interest in learning. This study aims to analyze the influence of learning styles on the learning outcomes of students in Islamic Elementary Schools using a qualitative approach through a literature review method. Research data were obtained through the collection and review of ten previous studies relevant to the topic of learning styles and learning outcomes of elementary school students or Islamic Elementary Schools. Data analysis techniques were carried out descriptively qualitatively through the process of reviewing, grouping, and drawing meaning from various previous research results. The results of the study indicate that learning styles have a significant relationship with student learning outcomes. Students who receive instruction tailored to their learning styles tend to understand the material more easily, are more engaged in learning, and achieve optimal learning outcomes. Therefore, paying attention to students' learning styles is a crucial factor in improving the quality of learning and student achievement in elementary madrasah